Process evaluation of a workplace-based health promotion and exercise cluster-randomised trial to increase productivity and reduce neck pain in office workers: a RE-AIM approach - Alyssa Welch; Genevieve Healy; Leon Straker; Tracy Comans; Shaun O'Leary; Markus Melloh; Gisela Sjøgaard; Michelle Pereira; Xiaoqi Chen; Venerina Johnston (BMC, 2020)
Abstract Background This study uses the RE-AIM framework to provide a process evaluation of a workplace-based cluster randomised trial comparing an ergonomic plus exercise intervention to an ergonomic plus health promotion intervention; and to highlight variations across organisations; and consider the implications of the findings for intervention translation. Method This study applied the RE-AIM (reach, effectiveness, adoption, implementation, maintenance) methodology to examine the interventions' implementation and to explore the extent to which differences between participating organisations contributed to the variations in findings. Qualitative and quantitative data collected from individual participants, research team observations and organisations were interrogated to report on the five RE-AIM domains. Results Overall reach was 22.7% but varied across organisations (range 9 to 83%). Participants were generally representative of the recruitment pool though more females (n = 452 or 59%) were recruited than were in the pool (49%). Effectiveness measures (health-related productivity loss and neck pain) varied across all organisations, with no clear pattern emerging to indicate the source of the variation. Organisation-level adoption (66%) and staffing level adoption (91%) were high. The interventions were implemented with minimal protocol variations and high staffing consistency, but organisations varied in their provision of resources (e.g. training space, seniority of liaisons). Mean adherence of participants to the EET intervention was 56% during the intervention period, but varied from 41 to 71% across organisations. At 12 months, 15% of participants reported regular EET adherence. Overall mean (SD) adherence to EHP was 56% (29%) across organisations during the intervention period (range 28 to 77%), with 62% of participants reporting regular adherence at 12 months. No organisations continued the interventions after the follow-up period. Conclusion Although the study protocol was implemented with high consistency and fidelity, variations in four domains (reach, effectiveness, adoption and implementation) arose between the 14 participating organisations. These variations may be the source of mixed effectiveness across organisations. Factors known to increase the success of workplace interventions, such as strong management support, a visible commitment to employee wellbeing and participant engagement in intervention design should be considered and adequately measured for future interventions. Trial registration ACTRN12612001154897; 29 October 2012.